Le résident secondaire au Sahel de Bizerte : représentations et perceptions du paysage de l’eau - Ghada Ben Abdesslem (Projets de Paysage)
The increasing number of people discovering this coastal area and building secondary residences there reveals the existence of different ways of perceiving the maritime landscape (Péron, 1994). Like any holiday destination, the coastline of the Bizerte Plain located in the north-east of Tunisia is a place that has been reinvented and redesigned according to the imagination and expectations of different social categories. Our article focuses on a category of inhabitants loyal to an alternative territory and residence: that of the secondary homeowners in the Bizerte Plain. Their different perceptions and representations of a water landscape are studied by means of semi-directive interviews with fifteen owners of secondary residences in the Bizerte Plain. Beyond analysing the sense of belonging, this study of the relationship to a water landscape seeks to highlight the way in which a place is appropriated in spatial terms through the daily habits of these secondary residents.